Knowledge, Attitude, And Practice Among Healthcare Professionals Regarding the Myths On COVID-19 Vaccination: A cross-sectional questionnaire study and demystification - Lokesh Kumar S; Zameera Naik; Arun Panwar; Sridhar M; Vaishali Keluskar; Ram Surath Kumar K (ACHSM, 2023)
Background: COVID-19 vaccine is the mighty weapon opted by all the countries across the globe in an attempt to eradicate the fatal COVID-19 pandemic. The myths on the COVID-19 vaccine are spreading widely, causing a hindrance to this noble preventive measure. The prevalence of such myths among healthcare professionals may be toxic and deadly. Aim & Objectives: To assess the knowledge, attitude, and practice of the healthcare professionals regarding the myths on COVID-19 vaccination and to demystify them. Materials and Methods: An 18-item questionnaire evaluating knowledge, attitude, and practice based on the existing myths on COVID-19 vaccination was circulated through Google Forms® among the 412 healthcare professionals of six disciplines belonging to a private University. The responses obtained were subjected to statistical analysis using SPSS® 20 software package. Results: A total of 385 health professionals participated in this study. The majority of them had medium knowledge (165) and positive attitude (273) with the mean knowledge and attitude scores of 3.82 ± 1.55 out of 6 and 4.3 ± 1.58 out of 7 respectively. Even though 312 participants got vaccinated, 72 of them failed to receive it. The knowledge scores showed a high statistically significant difference among the participants of different designations (p=0.001), but not with gender, field, and staff with different years of experience (p>0.05). The attitude scores were statistically different among participants of fields and designation (p<0.05) but not among genders (p=0.31) and staff with different years of experience (p=0.87). Knowledge and attitude scores showed a positive linear correlation and a high statistically significant difference (p<0.001). Conclusion: This study recommends more enhanced education programs on COVID-19 vaccination for the health professionals and demands an improved knowledge, attitude, and practice among them to achieve the goal of 100% vaccination so as to completely eradicate the COVID-19 pandemic.